Bacteriophage Therapy: Clinical Trials and Regulatory Hurdles - Furfaro, Lucy L.; Payne, Matthew S.; Chang, Barbara J. (Frontiers in Cellular and Infection Microbiology, 2018)
Increasing reports of antimicrobial resistance and limited new antibiotic discoveries and development have fuelled innovation in other research fields and led to a revitalization of bacteriophage (phage) studies in the Western world. Phage therapy mainly utilizes obligately lytic phages to kill their respective bacterial hosts, while leaving human cells intact and reducing the broader impact on commensal bacteria that often results from antibiotic use. Phage therapy is rapidly evolving and has resulted in cases of life-saving therapeutic use and multiple clinical trials. However, one of the biggest challenges this antibiotic alternative faces relates to regulations and policy surrounding clinical use and implementation beyond compassionate cases. This review discusses the multi-drug resistant Gram-negative pathogens of highest critical priority and summarizes the current state-of-the-art in phage therapy targeting these organisms. It also examines phage therapy in humans in general and the approaches different countries have taken to introduce it into clinical practice and policy. We aim to highlight the rapidly advancing field of phage therapy and the challenges that lie ahead as the world shifts away from complete reliance on antibiotics.